2016
DOI: 10.1177/1475090216679256
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and force analysis of a novel offshore crane combined compensation system

Abstract: Offshore cranes are widely used in offshore industry. However, because of the wave motion of the ship and the flexibility of the rope, the sway of payload is unavoidable and may put relevant operations in danger. Thus, compensation system is an essential part of offshore crane to ensure human safety and increase operation efficiency. In this article, a novel offshore crane combined compensation approach named four-post combined compensation is proposed based on the three-post direct ship motion compensation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It can be concluded that the longer the sleeve is, the larger the swing period and the smaller the swing frequency is. In accordance with formula (21), the sleeve elongation is inversely proportional to the payload swing period, and the frequency will decrease with the increase of sleeve elongation. e simulation results are consistent with the theoretical formula analysis, which further verifies the correctness of the simulation.…”
Section: Influence Of Sleeve Expansion and Contraction Amount On Payloadmentioning
confidence: 65%
See 1 more Smart Citation
“…It can be concluded that the longer the sleeve is, the larger the swing period and the smaller the swing frequency is. In accordance with formula (21), the sleeve elongation is inversely proportional to the payload swing period, and the frequency will decrease with the increase of sleeve elongation. e simulation results are consistent with the theoretical formula analysis, which further verifies the correctness of the simulation.…”
Section: Influence Of Sleeve Expansion and Contraction Amount On Payloadmentioning
confidence: 65%
“…Li et al [20] established the mathematical model of the load, and based on a timedelayed feedback, the control algorithm was proposed to antiload sway. Wang et al [21] proposed a novel offshore crane combined compensation approach named four-post combined compensation based on the three-post direct ship motion compensation; the mathematical models of fourpost combined compensation and three-post direct ship motion compensation were established uniformly. Lv et al [22] designed a 6-DOF active wave compensation cabledrive parallel robot that established its kinematic and dynamic model and explored swing suppression principle of the robot.…”
Section: Introductionmentioning
confidence: 99%
“…x P and z P can be found in equations (1) and 2; L PF can be found in equation (5). The expressions of F 2x , F 2z , F 3x , F 3z , i 2x , i 2z , i 3x and i 3z can be defined in a similar manner, no need to repeat here.…”
Section: Dynamic Modelmentioning
confidence: 99%
“…[1][2][3] However, there is no mature technology or equipment to control ship's roll, pitch and heave simultaneously until now, and this poses great challenges to offshore crane operations. 4,5 On one hand, the payload swing is inevitably induced by crane's luff or slew motion because of the crane system's underactuation. On the other hand, the ship motions are amplified by the long jib which in turn cause large swing of the payload.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al 5 presented a parallel wave compensation system to improve the anti-pendulation capability. Wang et al 6 designed a novel offshore crane combined compensation approach named four-post combined compensation based on the three-post direct ship motion compensation. They all had good wave compensation effect, but the mechanisms are complex and not easy to repair.…”
Section: Introductionmentioning
confidence: 99%